PENGARUH KEJELASAN SASARAN ANGGARAN, PENGENDALIAN AKUNTANSI, KOMPETENSI APARATUR PEMERINTAH DAERAH, SISTEM PELAPORAN, DAN KETAATAN PADA PERATURAN PERUNDANGAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (Studi Empiris pada Satuan Kerja Perangkat Dae - Imam Wahid; Azwir Nasir; Supriono ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aimed to determine the effect of budget goal clarity, accounting control, local government official competence, reporting system, and obedience to the laws and regulations on the performance accountability of government institution in Agam district. The population in this study is 27 government agencies. The sample use were are 51 respondents. The type of data used is primary data by using questionnaire. The analysis tool is using multiple regression with software SPSS version 21. The result show that: 1) budget goal clarity has significant effect on the performance accountability of government institution, 2) accounting control has not significant effect on the performance accountability of government institution, 3) local government official competence has significant effect on the performance accountability of government institution, 4) reporting system has significant effect on the performance accountability of government institution, and 5) obedience to the laws and regulation has significant effect on the performance accountability of government institution. All of the independent variables are influence the dependent variables as much as 52,1%, while 47,9% is influenced by other unclear variables.Keywords: budget goal clarity, accounting control, local government official competence, reporting system, and obedience